2012
DOI: 10.1111/j.1463-1318.2011.02609.x
|View full text |Cite
|
Sign up to set email alerts
|

Mild colonic diverticulitis can be treated without antibiotics. a case–control study

Abstract: Antibiotics can be omitted in selected patients with mild colonic diverticulitis and should be given on indication only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 32 publications
4
63
0
4
Order By: Relevance
“…Two retrospective case-control studies with 191 and 311 patients also found no differences in the frequency of complications and relapses of diverticulitis in patients with mild diverticulitis (according to Ambrosetti's criteria) treated with and without antibiotics [78,79]. …”
Section: Managementmentioning
confidence: 99%
“…Two retrospective case-control studies with 191 and 311 patients also found no differences in the frequency of complications and relapses of diverticulitis in patients with mild diverticulitis (according to Ambrosetti's criteria) treated with and without antibiotics [78,79]. …”
Section: Managementmentioning
confidence: 99%
“…It is notable, however, that the group who received antibiotics had more pronounced inflammation at baseline. A subsequent study reached the same conclusion [19]. These results should be interpreted with caution, as neither study was randomized, and the impact of selection bias on the outcomes must be considered.…”
Section: Management Of Acute Uncomplicated Diverticulitismentioning
confidence: 89%
“…This form of sigmoidal pathology is of particular importance against the background of impressive cyclic variations of hospital admissions for ´acute diverticulitis´ with highest frequencies during the summer months [25]. Because SCAD leads to segmental broadening of the affected colonic wall and may also cause a mesenteric reaction, this seasonal periodicity but also the new tendency towards a non antibiotic treatment of ´un-complicated diverticulitis´ [26,27] (possibly misdiagnosed and representing only minor summer infections) may be regarded important issues for a differential diagnosis of SCAD vs. ´true´ acute diverticulitis.…”
Section: Macropathology and Pathogenesis ▼mentioning
confidence: 99%